PERSEPSI TINGKAT KEPUASAN KELUARGA DI RT 03 RW 07 KELURAHAN MAKASAR - JAKARTA TIMUR TERHADAP PROGRAM KONVERSI MINYAK TANAH KE LIQUEFIED PETROLEUM GAS (LPG) - Rosita, Rahmi; Basuki, Rahmat (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2013)
The National program of converting Kerosene to Liquefied Petroleum Gas (LPG) aims to ensure the provision and procurement of fuel in the country and to reduce fuel subsidies in order to ease the financial burden of the Indonesian country. The purpose of this study is: (1) to analyze the characteristic of the family of the conversion program from kerosene to LPG (2) to determine their interests, satisfaction and perception towards the conversion program. The survey was conducted at RT 03/ RW 07 Kelurahan Makasar, Jakarta Timur. The research used descriptive statistical and library research methods. The sample of 30 respondents taken from 43 families as the population which chosen by probability sampling random. The data analyzed used Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results obtained are: (1) the families characteristic consists of: (a) dominated by families of ' 3d 4 member (b) aged of husbands/wives of 30 years old., (c) education; hubands/wives: senior high school, (d) occupation; husbands as businessman, wives as housewives, (e) point of sales: small grocery store than agent. (2) The matters of public concern in the use of LPG, including the price factor, resistance factor tube (security) and the availability of LPG 3 kg. (3) The majority of the families are satisfied with the program (3) the perceptions: (a) 85, 21% stated that the use of LPG is more beneficial, and economical cleaner and faster in cooking than using kerosene. (b) There is no force and they accepted the LPG as the kerosene substitute.